2022
DOI: 10.1177/10464964221105422
|View full text |Cite
|
Sign up to set email alerts
|

Team Citizenship Pressure: How Does It Relate to OCB and Citizenship Fatigue

Abstract: The aim of this research is to shed light on the phenomenon of citizenship pressure as a team-level construct. Building on the conservation of resources theory, the study used a moderated-mediation model to explore whether team organizational citizenship behavior (OCB) mediates the relationship between team citizenship pressure and team citizenship fatigue and whether this mediation is moderated by perceived supervisor support. Results from a study of 91 professional teams in the educational system indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 94 publications
1
12
0
Order By: Relevance
“…Based on a meta-analysis of the teachers’ OCB literature, perceived superior support is also valued as assurance that aid will be available from the supervisor when it is needed to carry out one’s job effectively and to deal with stressful situations (Eliyahu & Somech, 2022). On the basis of social exchange principles and reciprocity norms (e.g., Blau, 1964), when supportive leaders are seen as taking pride in their subordinates, compensating them fairly, teacher tend to display OCBs (Somech & Ohayon, 2020).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a meta-analysis of the teachers’ OCB literature, perceived superior support is also valued as assurance that aid will be available from the supervisor when it is needed to carry out one’s job effectively and to deal with stressful situations (Eliyahu & Somech, 2022). On the basis of social exchange principles and reciprocity norms (e.g., Blau, 1964), when supportive leaders are seen as taking pride in their subordinates, compensating them fairly, teacher tend to display OCBs (Somech & Ohayon, 2020).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Teachers play the crucial role in supporting continual improvement in teaching and learning (Clement & Rencewigg, 2020). Research has shown that teachers’ well-being and organizational citizenship behavior (OCB) leads to positive relationships with students and colleagues, as well as to higher students’ achievements (Eliyahu & Somech, 2022; Perera & John, 2020). At the same time, it is well established that teaching is associated with high workloads, strain, and stress, leading to low rates of job satisfaction and organizational commitment and to high turnover and burnout (Jehanzeb & Mohanty, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OCB is a crucial component in fostering a supportive psychological and emotional environment at the workplace (Eliyahu and Somech, 2023;Lee and Allen, 2002).…”
Section: Organizational Citizenship Behaviors and Citizenship Fatiguementioning
confidence: 99%
“…In this regard, employees experience intense societal or management pressure to do activities that are outside their regular responsibilities (Yildiz et al, 2022). As a result, citizenship fatigue caused by such extra roles incurs huge costs (Eliyahu and Somech, 2023) in terms of reduced future OCB engagement and even increased work-related counterproductive behaviors (Dongrey and Rokade, 2023). Hence, employees get disgruntled and experience citizenship fatigue when they are forced to work beyond their employment tasks.…”
Section: Compulsory Citizenship Behavior and Citizenship Fatiguementioning
confidence: 99%